Penetapan kadar flavonoid total perasan lemon (Citrus limon (L.) Osbeck) secara spektrofotometri UV-Vis - Christivanny Sheila Pravita; Crescentiana Emy Dhurhania (STIKes Surya Global Yogyakarta, 2023)
One of the fruits whose juice can function as an antibacterial is a lemon. This is related to the flavonoid content in lemons. The purpose of this study was to determine the total flavonoid content in local and imported lemon (Citrus limon (L.) Osbeck) juice using the UV-Vis spectrophotometric method. The filtered juice was used for qualitative analysis and quantitative analysis. Qualitative analysis using concentrated HCI reagent plus magnesium powder, 10% NaOH, and concentrated H2SO4 showed that lemon juice was positive for flavonoids. Quantitative analysis was performed using UV-Vis spectrophotometry with an operating time of 28 minutes, the maximum wavelength of 439 nm. The total flavonoid content in local lemon juice was 38.42 ± 0.448 mg QE/100 ml of juice, with a coefficient of variation obtained was 1.165%. The total flavonoid content in imported lemon juice was 39.76 ± 0.199 mg QE/100 ml of juice with a coefficient of variation was 0.501%.